Enrichment of pathogenic alleles in the brittle cornea gene, ZNF469, in keratoconus. (3rd June 2014) - Lechner, Judith; Porter, Louise F.; Rice, Aine; Vitart, Veronique; Armstrong, David J.; Schorderet, Daniel F.; Munier, Francis L.; Wright, Alan F.; Inglehearn, Chris F.; Black, Graeme C.; Simpson, David A.; Manson, Forbes; et al.
Abstract : Keratoconus, a common inherited ocular disorder resulting in progressive corneal thinning, is the leading indication for corneal transplantation in the developed world. Genome-wide association studies have identified common SNPs 100 kb upstream of ZNF469 strongly associated with corneal thickness. Homozygous mutations in ZNF469 and PR domain-containing protein 5 ( PRDM5 ) genes result in brittle cornea syndrome (BCS) Types 1 and 2, respectively. BCS is an autosomal recessive generalized connective tissue disorder associated with extreme corneal thinning and a high risk of corneal rupture. Some individuals with heterozygous PRDM5 mutations demonstrate a carrier ocular phenotype, which includes a mildly reduced corneal thickness, keratoconus and blue sclera. We hypothesized that heterozygous variants in PRDM5 and ZNF469 predispose to the development of isolated keratoconus. We found a significant enrichment of potentially pathologic heterozygous alleles in ZNF469 associated with the development of keratoconus ( P = 0.00102) resulting in a relative risk of 12.0. This enrichment of rare potentially pathogenic alleles in ZNF469 in 12.5% of keratoconus patients represents a significant mutational load and highlights ZNF469 as the most significant genetic factor responsible for keratoconus identified to date.